ROLE AND TYPES OF INSECTS IN SETTLEMENT AREAS OF SUNGAI PINANG VILLAGE IN SAMARINDA CITY - Ratnasari, Tiara Halidah; Hariani, Nova; Trimurti, Sus; Patang, Fatmawati (Universitas Tanjungpura, 2022)
The presence of arboreal insects in residential areas became indicator that the area is still overgrown with vegetation, whether flowering or not. The existence of vegetation in residential areas is referred to as Ruang Terbuka Hijau (RTH). The types of arboreal insects in Kelurahan Sungai Pinang Dalam Kota Samarinda have never been reported. This study aims to determine the role of the diversity of arboreal insect species in residential areas in Kelurahan Sungai Pinang Kota Samarinda. The sampling method for arboreal insects is a direct collection method using a sweeping net with a residential transect method for a month, once every two days in the morning and evening. The steps carried out in this study were collecting samples of arboreal insects, identifying and analyzing data on the index values of diversity, richness, evenness and dominance. The results showed that 26 genera of arboreal insects were found which were classified into 18 families and 8 orders. The diversity index value (H') of arboreal insect species in the morning is 2.7601 and in the afternoon is 2.4901. The dominance index value (C) obtained in the morning is 0.0880 and in the afternoon is 0.1192. For the evenness value, obtained in the morning of 0.8471 and in the afternoon of 0.8056. For the value of the wealth index (R), which was obtained in the morning was 4.1373 and in the afternoon was 3.6711. The results of data analysis show that the residential area in Kelurahan Sungai Pinang Dalam Kota Samarinda still has Ruang Terbuka Hijau (ecologically good) for arboreal insect life.